Effect of an siRNA Therapeutic Targeting PCSK9 on Atherogenic Lipoproteins: Prespecified Secondary End Points in ORION 1. Issue 13 (25th September 2018) - Ray, Kausik K.; Stoekenbroek, Robert M.; Kallend, David; Leiter, Lawrence A.; Landmesser, Ulf; Wright, R. Scott; Wijngaard, Peter; Kastelein, John J.P.
Abstract : Background: The ORION-1 trial (Trial to Evaluate the Effect of ALN-PCSSC Treatment on Low Density Lipoprotein Cholesterol [LDL-C]) demonstrated that inclisiran, an siRNA therapeutic that targets protease proprotein convertase subtilisin/kexin type 9 mRNA within hepatocytes, produces significant low-density lipoprotein cholesterol reduction. The effects of inclisiran on other lipids are less well described. Methods: ORION-1 was a phase 2 trial assessing 6 different inclisiran dosing regimens versus placebo. Participants with elevated low-density lipoprotein cholesterol despite receiving maximally tolerated statin therapy received a single-dose (200, 300, or 500 mg) or 2-dose starting regimen (100, 200, or 300 mg on days 1 and 90) of inclisiran or placebo. This prespecified analysis reports the percentage reductions in non–high-density lipoprotein cholesterol (non–HDL-C), apolipoprotein (apo) B, very-low-density lipoprotein cholesterol, lipoprotein(a), triglycerides, HDL-C, and apo A1 at the primary efficacy time point (day 180) with mixed-effect models for repeated measures. Additional prespecified analyses report time course of changes from baseline at each visit to day 210, interindividual variation in response, and lipid goal attainment. Results: The mean age of the 501 participants was 63 years, 65% were male, 69% had atherosclerotic cardiovascular disease, 73% used statins, and mean low-density lipoprotein cholesterol was 128 mg/dL. A single dose of inclisiran reduced apo B, non–HDL-C, and very-low-density lipoprotein cholesterol over 210 days. A second dose of inclisiran provided additional lowering of these lipids. At day 180, non–HDL-C was lowered dose-dependently: by 25% from 148±43 to 110±45 mg/dL in the 200-mg single-dose group and by 46% from 161±58 to 91±58 mg/dL in the 2-dose 300-mg group. For the same dosing regimens, apo B was reduced by 23% from 101±23 to 78±29 mg/dL and by 41% from 106±31 to 65±33 mg/dL ( P <0.001 for all groups versus placebo). In the 300-mg 2-dose group, all individuals experienced apo B and non–HDL-C reductions. There was larger interindividual variation in very-low-density lipoprotein cholesterol, triglycerides, and lipoprotein(a) reductions. In the 300-mg 2-dose group, the percentages of patients achieving guideline-recommended apo B goals for high- and very-high-risk patients at day 180 were 78% and 90%; 68% and 83% of participants achieved non–HDL-C <100 and <130 mg/dL. Conclusions: Inclisiran produces significant and prolonged reductions in atherogenic lipoproteins, suggesting that inhibiting the synthesis of protease proprotein convertase subtilisin/kexin type 9 through siRNA may be a viable alternative to other approaches that target protease proprotein convertase subtilisin/kexin type 9. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02597127. Abstract : Supplemental Digital Content is available in the text.